2019
DOI: 10.1101/773127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular correlates and therapeutic targets in T cell-inflamed versus non-T cell-inflamed tumors across cancer types

Abstract: The T cell-inflamed tumor microenvironment, characterized by CD8 T cells and type I/II interferon transcripts, is an important cancer immunotherapy biomarker. Tumor mutational profile may also dictate response with some oncogenes (i.e. WNT/β-catenin) known to mediate immuno-suppression. Building on these observations we performed a multi-omic analysis of human cancer correlating the T cell-inflamed gene expression signature with the somatic mutanome and transcriptome for different immune phenotypes, by tumor t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…We used a previously described T-cell inflammation score, 11 which correlates with other validated interferon-g gene signatures (Appendix). 12 This trial is registered with Clin-icalTrials.gov identifier: NCT02743819. The trial is closed to enrollment, but patients remain on treatment and in observation for safety and ongoing response assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a previously described T-cell inflammation score, 11 which correlates with other validated interferon-g gene signatures (Appendix). 12 This trial is registered with Clin-icalTrials.gov identifier: NCT02743819. The trial is closed to enrollment, but patients remain on treatment and in observation for safety and ongoing response assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with active CNS metastases were excluded (previously treated, stable CNS disease allowed); no prior anti-CTLA-4 antibody use in the metastatic setting was permitted. Full inclusion and exclusion criteria are listed in the study Protocol (online only [pp [12][13][14][15]). The study Protocol was reviewed and approved by the appropriate institutional review boards at each participating site.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Absence of PTEN leads to decreased T cell infiltration in melanoma with levels of CXCL10 transcripts decreased in PTEN mutant tumors (45). Emerging evidence demonstrates that IDH1 mutations are strongly correlated with non-T cell inflamed tumors and reductions in factors such as CXCL10 (46,47).…”
Section: Many Tumor Cells Are Genomically Unstable Which Results In the Activation Of Cell Intrinsicmentioning
confidence: 99%
“…CDC1 helps activating T cells and drives INF-g secretion of CD8+T (51). Studies have found that the Wnt signaling pathway can eliminate the gradient generation of chemokines required by DC (52).…”
Section: Discussionmentioning
confidence: 99%